LANDSLIDES AND SURFACE BREAKS OF THE 1911 MS 8.2 KEMIN EARTHQUAKE, KYRGYZSTAN - Delvaux D.; Abdrakhmatov K.E.; Lemzin I.N.; Strom A.L. (My University, 2001)
The 1911 Ms =8.2 Kemin (Kebin) earthquake in the northern Tien Shan (Kazakhstan, Kyrgyzstan) formed a complex system of surface ruptures nearly 190 km long and numerous landslides and rock avalanches up to tens of millions of cubic meters in volume. Judging from their distribution, six fault segments of the Kemin-Chilik and the Aksu fault zones with different strikes, dips, and kinematics were activated. The Kemin earthquake was one of the strongest events of a sequence of seismic catastrophes that affected the Kungei and Trans-iii-Alatau mountain ranges between 1887 and 1938. The effects of the Kemin earthquake are well documented in a monograph published soon after the event by K. I. Bogdanovich. In the framework of the European INCO·COPERNICUS program, the surface ruptures, landslides, and rockslides associated with this earthquake have been reexamined in detail. In addition, the large-scale tectonic setting of the Kemin-Chilik and Aksu fault zones has been re-evaluated, and their segments have been identified and described. The whole system forms a sinistral transpressional structure, which controls the formation of the mountain ranges between the Issyk-Kul' depression and the Kazakhstan block. The surface ruptures of the 1911 earthquake can presently be observed in the field over a total length of nearly 100 km and :generally reactivate longer-term cumulative paleoseismic fault scarps. The presence of well-expressed paleoseismic fault scarps and several tremendous ancient landslides in the Chon-Kemin, Chon-Aksu, and Aksu valleys can be considered as evidence for strong prehistoric earthquakes. Active fault, landslides, 1911 Kemin earthquake, Tien Shan, Kyrgyzstan
Keywords: Active fault; landslides; 1911 Kemin earthquake; Tien Shan; Kyrgyzstan